Postoperative occlusion of visual axis with fibrous membrane in the presence of anterior capsular phimosis in a patient with pseudoexfoliation syndrome: a case report. Issue 1 (December 2016) - Kim, Eung; Kim, Moosang; Lee, Seung-Jun; Han, Sang; Yang, Hee; Hyon, Joon
Abstract Background To report a case of postoperative fibrous membrane formation occluding the visual axis in the presence of anterior capsular phimosis in a patient with pseudoexfoliation syndrome. Case presentation A 79-year-old Asian woman with pseudoexfoliation syndrome underwent uneventful phacoemulsification and implantation of one-piece hydrophilic acrylic square-edged intraocular lens (Cristalens) in the right eye. Two months later, she had blurred vision in the right eye with the best-corrected visual acuity (BCVA) of 20/40. Formation of fibrous membrane occluding the capsulorhexis opening with contraction of anterior capsule was observed, which was confirmed by anterior segment optical coherence tomography. Clear visual axis was achieved by lysis of the membrane using Nd:YAG laser. The BCVA improved to 20/20. Conclusions Occlusion of the visual axis with fibrous membrane can develop in the presence of anterior capsular phimosis in a patient with pseudoexfoliation syndrome.